2015
DOI: 10.1038/npp.2015.283
|View full text |Cite
|
Sign up to set email alerts
|

Perirhinal Cortex mGlu5 Receptor Activation Reduces Relapse to Methamphetamine Seeking by Restoring Novelty Salience

Abstract: Rats that have self-administered methamphetamine (meth) under long access, but not short access, conditions do not recognize novel objects. The perirhinal cortex is critical for novelty detection, and perirhinal metabotropic glutamate 5 receptors (mGlu5) are downregulated after long-access meth. The novel positive allosteric modulator (PAM) 1-(4-(2,4-difluorophenyl) piperazin-1-yl)-2-((4-fluorobenzyl)oxy)-ethanone, or DPFE, demonstrates improved solubility compared with other mGlu5 PAMs, thus allowing brain-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…DPFE, a structurally distinct ligand relative to the three previous classes, was also included to offer further insight into the relationship between chemical scaffold and pharmacological outcome. As with CDPPB & VU0409551 behavioral studies have been conducted with DPFE (Gregory et al, 2013a; Peters et al, 2015), thereby allowing the potential to link in vivo efficacies with in vitro pharmacological fingerprints.…”
Section: Resultsmentioning
confidence: 99%
“…DPFE, a structurally distinct ligand relative to the three previous classes, was also included to offer further insight into the relationship between chemical scaffold and pharmacological outcome. As with CDPPB & VU0409551 behavioral studies have been conducted with DPFE (Gregory et al, 2013a; Peters et al, 2015), thereby allowing the potential to link in vivo efficacies with in vitro pharmacological fingerprints.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted after methamphetamine self-administration have similarly demonstrated both pro-cognitive effects of mGlu5 PAMs (5759) and anti-relapse effects of mGlu5 NAMs (60). The latter effect was observed following limited-access methamphetamine self-administration and extinction training (60).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, self-administration models that employ longer access to a drug also have received growing attention, likely owing to the noted differences between long- and short-access models (Ahmed and Koob 1998; Peters et al 2015; Reichel et al 2012). Long-access leads to a highly reproducible escalation of drug intake that is thought to reflect a more “addicted” state, versus short-access models that are thought to reflect “recreational” drug use (Ahmed and Koob 1998).…”
Section: Introductionmentioning
confidence: 99%